Characterization and Antimicrobial Resistance Profile of Pseudomonas Aeruginosa Isolated from Clinical and Environmental Samples - J.H, Doughari; A.A, Ahmad; K. M, Nafisat (Journal of Diseases, 2018)
Pseudomonas aeruginosa has emerged as a potential problematic Gram negative pathogen. The present study investigated the distribution of P. aeruginosa from the various clinical (wound and post-surgical wound) and environmental (water, industrial effluents and air) samples. The antibiotic resistance test was performed using the disc diffusion method according to NCCLS guidelines. Multidrug resistant genes among the isolates were characterized using PCR. 18 of the isolates with multidrug resistance showed least resistance to ceftazidime (23 %), gentamicin (20 %) and ciprofloxacin (31 %) from clinical isolates and 60, 38.5 and 60 % respectively from environmental isolates. Over 78 % of the isolates were polyvalent 1 strains, 17 % were polyvalent 2 and 5 % were polyvalent 3 strains. Polyvalent 1 were mostly strains from clinical samples while polyvalent 2 and 3 were strains from both (clinical and environmental) samples investigated. PCR analysis of multidrug resistant P. aeruginosa indicates that, PA-SS species specific signature sequences were present in all (100%) the isolates investigated. There was high emergence of antibiotic resistance in the environment and hospital investigated. Proper monitoring, regulating indiscriminate use of chemicals in the environment and restricting the use of antibiotics without susceptibility tests or prescription by a qualified physician should be adopted.